2014
DOI: 10.1111/evo.12519
|View full text |Cite
|
Sign up to set email alerts
|

Do age-specific survival patterns of wild boar fit current evolutionary theories of senescence?

Abstract: Actuarial senescence is widespread in age-structured populations. In growing populations, the progressive decline of Hamiltonian forces of selection with age leads to decreasing survival. As actuarial senescence is overcompensated by a high fertility, actuarial senescence should be more intense in species with high reproductive effort, a theoretical prediction that has not been yet explicitly tested across species. Wild boar (Sus scrofa) females have an unusual life-history strategy among large mammals by asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 57 publications
(82 reference statements)
3
22
1
Order By: Relevance
“…; Gamelon et al. ). Although it has already been shown that the onset of senescence covaries with other time variables to shape the pace of life in mammals and birds (Jones et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Gamelon et al. ). Although it has already been shown that the onset of senescence covaries with other time variables to shape the pace of life in mammals and birds (Jones et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Gamelon et al. ). These recent findings emphasize that the onset of senescence could potentially better assess the potential costs of sexual selection in terms of actuarial senescence.…”
Section: Survey Of Comparative Analyses Investigating the Relationshimentioning
confidence: 97%
“…We thus constrained survival of 1 to be equal to 0.99, and we fitted a Generalized Additive Model to obtain the age-specific mortality curve. Since both theoretical and empirical evidence reveal that actuarial senescence does not start prior to the age of sexual maturity2829, the onset of actuarial senescence was defined as the age at which the annual mortality rate was the lowest between the age at sexual maturity and the age at which 90% of individuals from the initial cohort have died (Fig. 1, Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in free-ranging ungulates, males suffer from a much steeper rate of senescence than females [89]. Such differences have been mainly interpreted as a consequence of sexual selection, with costs associated with polygynous mating systems causing faster senescence in males than in females ( [85][86][87]90]; but see [91]). Indeed, defending a group rspb.royalsocietypublishing.org Proc.…”
Section: (B) Sex-differences In Ageing Patternsmentioning
confidence: 99%